Social Media and Direct Selling of Menara Kanaya Apartment by Perumda Pembangunan Sarana Jaya Daerah Khusus Jakarta - Putri, Poppy Pertiwi; Widjayanti, Arifiani; Wibowo, Eddy Kusponco (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Indonesia's property companies have grown rapidly in recent years. The strategy includes social media marketing and direct sales to generate public buying interest, as used by Perumda Pembangunan Sarana Jaya, owned by Daerah Khusus Jakarta Local Government. This research aims to analyse the influence of social media marketing and direct selling on the purchase interest of Menara Kanaya Perumda Pembangunan Sarana Jaya, Jakarta. The study is based on a survey of 120 respondents, using a quantitative methodology. The results indicate that social media marketing and direct selling have a positive and significant influence on the purchase intention of Menara Kanaya Perumda Pembangunan Sarana Jaya. Social media marketing has a positive and significant influence of 57.7% on purchase interest, direct selling has a positive and significant influence of 47.1% on purchase interest, and simultaneously, social media marketing and direct selling have a positive and significant influence of 63.3% on purchase interest. The remaining 36.7% is determined by other factors not included in this study.